AFTER CLASS ACTIVITIES AND THEIR USAGE IN TEACHING ENGLISH - Ataxojayev Toxirjon Maxmudjonovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article deals with after class activities which are used in teaching foreign languages at secondary schools, the forms of after class activities, the organization of after class activities, the role of after class activities in language learning.